Analysis of the Bearing Capacity of a Steel Structural Member after Reinforcement - Chen Chen; Yake Tang; Liang Zhang; Kai Niu; Xiangrui Meng; Meng Yang; Juncai Liu (Advances in Civil Engineering)
To improve the bearing capacity of existing angle steel structures, a new and cost-effective reinforcement method for increasing the load-bearing capacity is proposed. This method uses steel pipes as auxiliary materials and clamps the reinforced angle steel and the auxiliary materials through fixtures to ensure that they are deformed together. The influence of the fixture spacing, the size of the reinforced angle steel member, the slenderness ratio of the members, the size of the auxiliary steel pipe, and other parameters on the reinforcement effect is studied. The results show that the smaller the fixture spacing is, the more obvious the improvement of the bearing capacity is, and the reasonable fixture spacing is related to the angle steel leg width. The larger the slenderness ratio of the member is, the more obvious the reinforcement effect of the scheme is. The steel pipe size has a significant impact on the reinforcement effect of the scheme.